Combining single-cell RNA sequencing data and network pharmacology to explore the mechanism of action of Dayuan Yin in the treatment of acute lung injury - Lei Zhang; Wei Zhu; Zepeng Zhang; Yu Huang (KeAi Communications Co., Ltd., 2023)
Background: This study aimed to analyze the usefulness of combined single-cell RNA sequencing data and network pharmacology in understanding the molecular regulation mechanism of Dayuan Yin (DYY) in acute lung injury (ALI). Methods: The single-cell ALI dataset GSE224938 was acquired from the Gene Expression Database and cellular heterogeneity was examined using the Seurat software package. Differential expression analysis was conducted using the R software to identify genes with significant expression differences. The active constituents and therapeutic targets of DYY were acquired from the Traditional Chinese Medicine Systems Pharmacology (TCMSP) database. Subsequently, the protein-protein interaction (PPI) networks, gene ontology (GO), and Kyoto Encyclopedia of Genes and Genomes (KEGG) were employed to analyze the key targets. A visual network depicting the interaction between compounds, targets, and pathways was constructed, and the CytoNCA plug-in was utilized to identify core targets. The active component-core target relationship was validated using MOE, AutoDockTools, AutoDockVina, and other software. Finally, a preliminary experiment was conducted using the lipopolysaccharide-induced acute lung injury (ALI) rat model. Results: In total, 5243 significantly differentially expressed genes were identified in ALI, and 260 genes were identified as DYY targets. Then, 81 target genes were identified at the intersection between drugs and diseases. The identified core target genes included PIK3R1, IL-1β, IL-6, ICAM1, and CCL2. GO analysis was mainly involved in cellular inflammatory response, dual regulation of cell apoptosis, and coordinated migration. KEGG analysis showed enrichment in inflammatory pathways. The major active components were well connected with IL-1β. DYY could significantly reduce the phosphorylation expression of PI3K, Akt, and NF-κBp65 in the lung tissue of ALI rats, and regulated the activation of related inflammatory cells. Conclusions: We successfully screened the potential active ingredients of DYY for the treatment of ALI. In addition, in vivo experiments preliminarily verified the predictions of network pharmacology, showing that DYY can inhibit the PI3K/Akt/NF−КВ signaling pathway, reduce cytokine release and regulate the number of inflammatory cells, providing an alternative for ALI treatment.